The Development of Protecting Elderly Persons’ Rights in Protection Home for the Destitute - Thepparp, Rungnapa; Rattanarat, Nirumon (Journal of Social Work and Social Administration, 2024)
The purpose of this research is to examine the protection and access to rights for the elderly and those approaching old age (50 years and above) in Protection Centers for the Destitute. Additionally, it aims to develop guidelines for improving rights protection and to propose policies for this demographic within these centers. Quantitative data were collected from 919 clients aged 50 and above from 6 Protection Centers for the Destitute, while qualitative data were gathered from 69 informants through in-depth interviews, focus group discussions, and exchange forums. The findings revealed that: (1) Protection Centers for the Destitute are experiencing an intensely aging population, with over 28 percent of users being 60 years or older, highlighting the inadequacy of current services tailored specifically for elderly users; (2) The format and access to rights for service users are primarily protected as "destitute people," with significant gaps in protection specific to "elderly people"; (3) Guidelines for improving rights protection for the elderly in shelters include: (a) legal improvement and enforcement measures, (b) integration of cooperation among various agencies with an elderly-centric approach, and (c) specific rights protection services for the elderly in shelters. (4) Policy recommendations include: (a) enhancing the protection of rights for destitute elderly individuals to ensure they live with dignity and human value, and (b) preventing elderly individuals from entering shelters by promoting self-reliance and quality living within their communities under the concept of aging in place. This research underscores the urgent need for tailored services and policies that address the unique needs of the elderly in destitute conditions, ensuring their rights and dignity are upheld.